2010
DOI: 10.1007/bf03245857
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamics of Cobalt(III) Schiff base complexes in various solvents

Abstract: The electronic and steric effects of some Schiff bases and the solvent on the thermodynamic parameters of the pentacoordinate Co(III) Schiff base complexes were studied. The formation constants and the thermodynamic parameters were measured spectrophotometrically for 1:1 adduct formation of the complexes as acceptors with tributylphosphine (PBu 3 ) as donor, in some solvents (acetonitrile, tetrahydrofuran, butanol, ethanol and N,N-dimethylformamide) in constant ionic strength (I = 0.01 M, sodium perchlorate) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…The negative sign of the ΔS suggests that the degree of structural complexity (arrangement) of the activated complex was lower than that of the starting reactants and the decomposition reactions are slow reactions. The ΔH o value and its sign, is dependent on the heat of formation of the complex and the solvent effect 20 , in all cases, it is found that the ΔHº values are positive, so the Reactions are endothermic. Further, degrades with the subsequent loss of (benzene ring) species forming species with peak at m/e= 290.…”
Section: Kinetics Of Thermal Decomposition Of Some Prepared Complexesmentioning
confidence: 85%
“…The negative sign of the ΔS suggests that the degree of structural complexity (arrangement) of the activated complex was lower than that of the starting reactants and the decomposition reactions are slow reactions. The ΔH o value and its sign, is dependent on the heat of formation of the complex and the solvent effect 20 , in all cases, it is found that the ΔHº values are positive, so the Reactions are endothermic. Further, degrades with the subsequent loss of (benzene ring) species forming species with peak at m/e= 290.…”
Section: Kinetics Of Thermal Decomposition Of Some Prepared Complexesmentioning
confidence: 85%
“…The d  π* charge transfer depended on the charge density in the Schiff base. In the thermodynamic studies of the five-coordinated complexes with amines and formation of six-coordinated complexes this band shifts to lower energy because of the increasing charge density over the metal ion and the d  π* charge transfer was easier, so a new absorption band at 450-470 nm region (shoulder, d  π*) appeared and the absorption band at 650-750 nm vanished [33] (see Figure 1). The isosbestic point shows that there is one equilibrium system in the adduct formation.…”
Section: Uv-vis Spectral Studiesmentioning
confidence: 99%
“…The TEM images further revealed the stabilization of copper and zinc nanoparticles due to interaction with the (HL) ligand. This stabilization facilitates penetration of tumor cell membrane and cause the destruction of tumor cell by CuNPs and ZnNPs (50,51) . The CuNPs and ZnNPs sizes are of 50, 60 nm respectively.…”
Section: 8transmission Electron Microscopy (Tem)mentioning
confidence: 99%